An international dataset on organic molecule concentrations in soil and related kitchen garden crops - Céline Laurent; Laure Genies; Géraldine Bidar; Elodie-Denise Ripamonti-Chenot; Camille Dumat; Corinne Hulot; Franck Marot; Christophe Schwartz; Stéphanie Ouvrard (Scientific Data)
Abstract Kitchen garden crops offer many environmental, socio-economic and health benefits but can also result in land use changes that may increase citizens’ exposure to pollutants. In this context, a dataset of organic molecules, based on an analysis of scientific literature was created, entitled BAPPOP (BAse de données sur la contamination des Plantes Potagères par les molécules Organiques Polluantes, i.e. dataset on contamination of kitchen garden plants by organic pollutants). BAPPOP compiles 6246 entries collected from 87 publications and 3 reports linking data on organic molecule’ concentrations in kitchen garden soil and crops. Additional information relative to the conditions for which the data have been obtained complete the dataset: organic molecule descriptions, soil properties, plant descriptions and treatments, experimental and analytical methods, as well as bibliographic information. This dataset is suitable for various stakeholders involved in environmental analyses both to compare site specific results to scientific literature data and secondly to predictively evaluate organic molecule’ concentrations and their transfer to kitchen garden crops based on the soil concentration.